Controlling the Flexibility of MIL‐88A(Sc) Through Synthetic Optimisation and Postsynthetic Halogenation. Issue 48 (29th June 2022) - Walshe, Catherine A.; Thom, Alexander J. R.; Wilson, Claire; Ling, Sanliang; Forgan, Ross S.
Abstract: Breathing behaviour in metal‐organic frameworks (MOFs), the distinctive transformation between a porous phase and a less (or non) porous phase, often controls the uptake of guest molecules, endowing flexible MOFs with highly selective gas adsorptive properties. In highly flexible topologies, breathing can be tuned by linker modification, which is typically achieved pre‐synthetically using functionalised linkers. Herein, it was shown that MIL‐88A(Sc) exhibits the characteristic flexibility of its topology, which can be tuned by 1) modifying synthetic conditions to yield a formate‐buttressed analogue that is rigid and porous; and 2) postsynthetic bromination across the alkene functionality of the fumarate ligand, generating a product that is rigid but non‐porous. In addition to providing different methodologies for tuning the flexibility and breathing behaviour of this archetypal MOF, it was shown that bromination of the formate‐bridged analogue results in an identical material, representing a rare example of two different MOFs being postsynthetically converted to the same end product. Abstract : The flexibility of the MOF MIL‐88A(Sc) is described and compared to its well‐established Fe analogue. Its breathing behaviour can be controlled through installation of formate bridges during synthesis that ensure rigidity by structural buttressing, or by postsynthetic bromination of the fumarate linker to induce rigidity by the steric influence of the bulky linker substituents.